MODEL PEMBELAJARAN INTEGRATIF PADA BIOLOGI PERKEMBANGAN HEWAN: ANALISIS KEBUTUHAN PENGEMBANGAN - M. Haviz; Lufri Lufri; Ahmad Fauzan; Z. Mawardi Effendi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
The report is a part of developing integrative learning model (MPI) on the biology of animal development. The research objective was to determine the needs analysis of developing MPI on the biology of animal development at STAIN Batusangkar. The research use Plomp model. The data obtained will be analyzed by data reduction, data presentation and drawing conclusions. The result showed that philosophy of STAIN Batusangkar is an integration. Analysis of the characteristics of students showed that students of STAIN Batusangkar has a heterogeneous background of the aspects of capability. These results are based on the findings of the Academic Performance Index, schools and majors while undergoing studies in high school, the course pre-condition and the results of multiple intelegencie test. Developmental of biology material is characterized by the facts, concepts, principles and theories. In conclusion, the research is a part of activity that supports of developing MPI on the biology of animal development at STAIN Batusangkar.Kata kunci: analisis karakteristik, model pembelajaran integratif, biologi perkembangan hewan